Medical Equipment Maintenance Management System with Fingerprint Authentication - Abu Hanifah, Nadhirah; Wan Kairudin, Wan Nur Hafsha; Mohd, Ezri; Ismail, Muhammad Nafis (Evolution in Electrical and Electronic Engineering, 2021)
Medical equipment in hospital requires an effective maintenance system to record every maintenance issues, tracking the person in charge for that equipment and the date in and out from the location of that equipment. Hospitals in Malaysia still lacks of systematic equipment maintenance management system where most of the hospitals still using manual methods to record and monitor equipment in and out from the location for maintenance purposes. In fact, manual methods like this are time consuming, prone to errors and loss of records. Considering the importance of a proper system to record the medical equipment maintenance, the purpose of this paper is to accomplish the objectives to develop a medical equipment maintenance management system for tracking equipment for maintenance allows automatically tracking the maintenance history of medical equipment using Microsoft Visual Basic Studio integrated with Arduino IDE for fingerprint identification, consider as a key to recognize the identity of users. Thus, based on the result obtained, it is proved that the accuracy of the fingerprint identification is highly accurate and the probability of having the same fingerprint with somebody else is not likely to occur. The medical equipment maintenance management system developed able to record and store essential maintenance data for future reference.